Chemical Composition of Essential Oil and Screening of Antiproliferative Activity of Paronychia argentea Lam. Aerial Parts: an Ethno-Medicinal Plant from Jordan - Alhourani, Noor; Hudaib, Mohammad; Bustanji, Yasser; Alabbassi, Reem; Kasabri, Violet (Jordan Journal of Pharmaceutical Sciences, 2020)
Background & Aim: in the present study, composition of the volatile (essential) oil hydrodistilled from flowering tops of Paronychia argentea Lam. (Caryophyllaceae) grown in Jordan was examined. Methods: Analyses were performed by means of GC and GC-MS. In-vitro cytotoxicity of the aqueous and alcohol extracts of the plant aerial parts was screened against different cell lines; human breast adenocarcimoma (MCF-7), colorectal adenocarcinoma (Caco-2), pancreatic carcinoma (Panc-1) as well as normal fibroblast cells. Results: Forty-one components were identified in the essential oil from flowering tops of P. argentea. The oil was found to be very rich in sesquiterpenes (60.96%), while, 6,10,14-trimethyl-2-pentadecanone (16.14%), a non-terpenoidal ketone, was identified as principal component of the oil. Other major identified components included o-cymene (7.51%), allo-aromadendrene epoxide (6.99%), isolongifolan-7-a-ol (5.19%), 9-epi-E-caryophyllene (4.89%), and isobicyclogermacrenal (4.33%). Conclusion: Hydrodistillation of P. argentea EO revealed its richness in sesqueterpenes, while the cytotoxicity assays of the plant extracts failed to conclude any antiproliferative activity against the tested cancer cell lines over the investigated concentration range.